Redox Status Is the Mainstay of SARS-CoV-2 and Host for Producing Therapeutic Opportunities - Anand Thirupathi; Yaodong Gu; Zsolt Radak; Ricardo A Pinho (MDPI AG, 2022)
Over hundreds of years, humans have faced multiple pandemics and have overcome many of them with scientific advancements. However, the recent coronavirus disease (COVID-19) has challenged the physical, mental, and socioeconomic aspects of human life, which has introduced a general sense of uncertainty among everyone. Although several risk profiles, such as the severity of the disease, infection rate, and treatment strategy, have been investigated, new variants from different parts of the world put humans at risk and require multiple strategies simultaneously to control the spread. Understanding the entire system with respect to the commonly involved or essential mechanisms may be an effective strategy for successful treatment, particularly for COVID-19. Any treatment for COVID-19 may alter the redox profile, which can be an effective complementary method for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) entry and further replication. Indeed, redox profiles are one of the main barriers that suddenly shift the immune response in favor of COVID-19. Fortunately, several redox components exhibit antiviral and anti-inflammatory activities. However, access to these components as support elements against COVID-19 is limited. Therefore, understanding redox-derived species and their nodes as a common interactome in the system will facilitate the treatment of COVID-19. This review discusses the redox-based perspectives of the entire system during COVID-19 infection, including how redox-based molecules impact the accessibility of SARS-CoV-2 to the host and further replication. Additionally, to demonstrate its feasibility as a viable approach, we discuss the current challenges in redox-based treatment options for COVID-19.